ORTHODONTIC TREATMENT AND CHEMICAL AGENTS IN CONGENITAL MALFORMATIONS OF CEPHALIC REGION - Kamel Earar; Gabriel Bogdan Carp; Corina Cecilia Manole Palivan; Marius Maris; G.G. Condurache; Gabriel Drug; Mădălina Nicoleta Matei (Romanian Society of Oral Rehabilitation, 2020)
he state of health of the dento-maxillary apparatus presupposes the morpho-functional integrity and the harmonious, proportional development of all the component elements, so that the relations between teeth, between arches and jaws are within the limits of phylogenetic variables, and their functioning is coordinated, automated through an integrated adjustment system that stimulates the consolidation of shapes. The ideal in orthodontics is to obtain an optimal morpho-functional function of the dento-maxillary apparatus. In order to better understand and be able to explain some aspects of intrauterine development, growth and differentiation, modern physiology has sought to decipher the most intimate aspects of the plantar filter, the way through which all the influences of the external environment, represented by the mother's body, are transmitted to the fetus. Malformation is invalidated by its consequences on multiple levels: aesthetic, psychological, speech, nutrition, associated malformations. Material and method: The study includes 54 cases of cleft lip and palate: 36 are male and 18 are female. Results and discussions: The causal factors act in the first 10 weeks of pregnancy in the organogenesis phase of the embryo, when the structures of the middle part of the face are formed. The condition can be diagnosed from the fifth month of pregnancy, by ultrasound examination, but this is not always possible, depending on the position of the fetus, but also on the performance of the device, as well as the experience of the doctor performing ultrasound. Conclusions: Risk of splitting labiale- maxillo-palatine, is approximately equal for untreated maternal epilepsy or under treatment. Regarding maternal age, the study revealed a maximum risk in young mothers.